Detection of mcr‐1‐positive Escherichia coli in slaughterhouse wastewater collected from Dawen river. Issue 5 (7th May 2021) - Wang, Xinxing; Li, Li; Sun, Fengxia; Wang, Jinji; Chang, Weishan; Chen, Fengmei; Peng, Jun
Abstract: Background: Low levels of mcr‐1 were detected in Escherichia coli from wastewater samples across the world; hence, further monitoring and management of accumulation of mcr‐1 ‐positive bacteria in wastewater are urgently recommended. Objectives: In this study, we have reported the detection of E. coli strains carrying the colistin resistance gene mcr‐1 in slaughterhouse wastewater discharged into Dawen river. Methods: Twenty samples were collected aseptically and subjected to polymerase chain reaction (PCR) analysis, multilocus sequence typing and antibiotic resistance tests. Conjugation tests were also performed. Results: The screening results showed a positive rate of 20% (4/20), which suggested that the mcr‐1 gene had polluted the environment of the river. The mcr‐1 gene had successfully transferred from the donor to recipient cells, which showed the possibility of horizontal transfer of mcr‐1 and subsequently, the formation of multidrug resistant bacteria in the river. Conclusions: Our findings demonstrated a high occurrence of colistin‐resistant E. coli carrying the mcr‐1 gene on transferrable plasmids in slaughterhouses and indicated their dissemination into river. Large‐scale cross‐border cooperation would be required for the effective control of the spread of antibiotic‐resistant bacteria. Abstract : Large‐scale cross‐border cooperation would be required for the effective control of the spread of antibiotic‐resistant bacteria. Our findings demonstrated the high occurrence of colistin‐resistant E. coli carrying mcr‐1 on transferrable plasmids in slaughterhouses and indicated their dissemination into river.